Delivering justice - Hodges, C (Intersentia, 2019)
The legal system needs to slay some myths. Focusing on access to justice avoids the critical issue of whether justice is actually delivered, in enough individual cases and as a whole. Retaining an adversarial dispute resolution model avoids the reality that it cannot work absent a consistently reliable source of funding, and more investigative models are cheaper and quicker. Focusing on deterrence avoids the fact that the empirical evidence that imposing deterrent sanctions has at best limited effect of the future behaviour of people or organisations, and that those regulators and organisations that have based their approaches on behavioural psychology and ethical cultures are notably effective in affecting change and future behaviour. In short, for all these reasons, our approach to dispute resolution is now out-of-date. There has been diversification in techniques (mediation and other ADR techniques in addition to adjudication), in technologies (online process, use of artificial intelligence), in pathways (Ombudsmen have replaced lawyers and courts in consumer-trader disputes, and are set to do so in the property sector; new regulatory bodies have been created for disputes involving small businesses), and in functions (Ombudsmen and regulators use data from inquiries and disputes as tools of market surveillance and behavioural intervention). The reality is that we need a new start to look objectively at considerable diversity and to design a new system that integrates all techniques, technologies, pathways and functions into a single coordinated system. This article summarises a recent holistic review of the system in England (and partly Wales) and outlines its conclusions.